From Arabic Style toward Javanese Style: Comparison between Accents of Javanese Recitation and Arabic Recitation - Nur Faizin (Kawalu: Journal of Local Culture, 2017)
Moslem scholars have acceptedmaqamat in reciting the Quran otherwise they have not accepted macapat as Javanese style in reciting the Quran such as recitationin the State Palace in commemoration of Isra` Miraj 2015. The paper uses a phonological approach to accents in Arabic and Javanese style in recitingthe first verse of Surah Al-Isra`. Themethod used here is analysis of suprasegmental sound (accent) by usingSpeech Analyzer programand the comparison of these accents is analyzed by descriptive method. By doing so, the author found that:first, there is not any ideological reason to reject Javanese style because both of Arabic and Javanese style have some aspects suitable and unsuitable with Ilm Tajweed; second, the suitability of Arabic style was muchthan Javanese style; third, it is not right to reject recitingthe Quran with Javanese style only based on assumption that it evokedmistakes and errors; fourth, the acceptance of Arabic style as the art in reciting the Quran should risedacceptanceof the Javanese stylealso. So, rejection of reciting the Quranwith Javanese style wasnot due to any reason and it couldnot be proofed by any logical argument. Keywords: Recitation, Arabic Style, Javanese Style, Quran.